1999
DOI: 10.2166/wst.1999.0484
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humic Substance Alteration during Soil Passage on their Treatment Behaviour

Abstract: Humic substances are not major objectives of water treatment in drinking water supply. But, as they often influence the treatment efficiency or participate in treatment reactions, their behaviour in the treatment process can significantly determine the process design. A very effective pretreatment step can be achieved by soil passage (e. g. bank filtration or slow sand filtration) which is usually involved in German surface water treatment processes. In this study transport phenomena of humic matter during und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Different components of NOM exhibit different transport behavior during surface water infiltration. Several studies have indeed demonstrated that the mobility of NOM in the subsurface increases with decreasing molecular weight and hydrophobicity (20)(21)(22). These results suggest that the smaller and more hydrophilic fraction of NOM may dominate the NOM-facilitated transport of contaminants in groundwater.…”
Section: Removing Natural Organic Mattermentioning
confidence: 95%
“…Different components of NOM exhibit different transport behavior during surface water infiltration. Several studies have indeed demonstrated that the mobility of NOM in the subsurface increases with decreasing molecular weight and hydrophobicity (20)(21)(22). These results suggest that the smaller and more hydrophilic fraction of NOM may dominate the NOM-facilitated transport of contaminants in groundwater.…”
Section: Removing Natural Organic Mattermentioning
confidence: 95%
“…The aromatic carbon of these isolates decreased significantly only during long travel times (2 to 8 years of transport) with relatively small changes in DOC concentration. Kivimaeki et al (1998) and Gerlach and Gimbel (1999) also observed that the highest molecular weight fractions of organic matter were removed during the initial phase of infiltration because the collision efficiencies greatly increased with increasing molecular weight. These findings point to the long-term transformation of remaining organic matter during travel through the subsurface towards well-aged fulvic acids, while non-humic material is biodegraded and humic substances are adsorbed during the initial phase of infiltration.…”
Section: Dissolved Organic Carbonmentioning
confidence: 97%
“…These findings point to the long-term transformation of remaining organic matter during travel through the subsurface towards well-aged fulvic acids, while non-humic material is biodegraded and humic substances are adsorbed during the initial phase of infiltration. A fundamental understanding of the removal mechanisms for humic substances in RBF systems is still missing, although most studies suggest a combination of initial adsorption followed by biodegradation (Sontheimer, 1991;Gerlach and Gimbel, 1999). The accumulation of organic matter in RBF systems due to the continuous deposition of humic substances usually does not occur due to microbiologically induced degradation of sorbed humic substances (Gerlach and Gimbel, 1999).…”
Section: Dissolved Organic Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Different components of NOM can have a substantial effect on its treatability, and its mobility in the subsurface, its reactivity with chlorine, and the speciation of the DBPs formed as a result of this reaction (Aiken and Cotsaris 1995; Croue et al 1999). The mobility of NOM in the subsurface increases with decreasing molecular weight and hydrophobicity, which suggests that smaller and more hydrophilic fraction of NOM may dominate NOMfacilitated transport of contaminants in groundwater (McCarthy et al, 1993;Ludwig et al, 1997;Gerlach and Gimbel, 1999). While the overall concentrations of organic DBP precursors are effectively reduced during bank filtration, the reductions appear to be largely the result of the reduction in NOM concentration rather than a consistent change in NOM character (Weiss et al, 2004).…”
Section: Organics Removalmentioning
confidence: 99%